Are Young Swimmers Short and Middle Distances Energy Cost Sex-Specific? - Massini, Danilo A.; Almeida, Tiago A. F.; Vasconcelos, Camila M. T.; Macedo, Anderson G.; Espada, Mário A. C.; Reis, Joana F.; Alves, Francisco J. B.; Fernandes, Ricardo J. P.; Pessôa Filho, Dalton M. (Frontiers in Physiology, 2021)
This study assessed the energy cost in swimming (C) during short and middle distances aiming to analyse the sex-specific responses of C during supramaximal velocity and whether body composition account to the expected differences. Twenty-six swimmers (13 men and 13 women: 16.7±1.9 vs. 15.5±2.8 years old and 70.8±10.6 vs. 55.9±7.0 kg of weight) performed maximal front crawl swimming trials in 50, 100 and 200 m. The oxygen uptake (V̇O2) was analysed along the tests (and post-exercise) through a portable gas analyser connected to a respiratory snorkel. Blood samples were collected before and after exercise (at 1st, 3rd, 5th and 7th min) to determine blood lactate concentration ([La-]). The lean mass of the trunk (LMTrunk), upper limb (LMUL) and lower limb (LMLL) were assessed using dual X-ray energy absorptiometry (DXA). Anaerobic energy demand was calculated from the phosphagen and glycolytic components, with the first corresponding to the fast component of the V̇O2 bi-exponential recovery phase and the second from the 2.72 ml×kg-1 equivalent for each 1.0 mmol×L-1 [La-] variation above the baseline value. The aerobic demand was obtained from the integral value of the V̇O2 vs. swimming time curve. The C was estimated by the rate between total energy releasing (in Joules) and swimming velocity. The sex effect on C for each swimming trial was verified by the two-way ANOVA (Bonferroni post hoc test) and the relationships between LMTrunk, LMUL and LMLL to C were tested by Pearson coefficient. The C was higher for men than women in 50 (1.8±0.3 vs. 1.3±0.3 kJ×m-1), 100 (1.4±0.1 vs. 1.0±0.2 kJ×m-1) and 200 m (1.0±0.2 vs. 0.8±0.1 kJ×m-1) with p<0.01 for all comparisons, as well as C differed between distances for each sex (p<0.01). The regional LMTrunk (26.5±3.6 vs. 20.1±2.6 kg), LMUL (6.8±1.0 vs. 4.3±0.8 kg) and LMLL (20.4±2.6 vs.13.6±2.5 kg) for men vs. women were significantly correlated to C in 50 (R2adj=0.73), 100 (R2adj=0.61) and 200 m (R2adj=0.60, p<0.01). Therefore, the increase in C with distance is higher for men than women and determined by the lean mass in trunk, upper and lower limbs, independently of the differences in body composition between sexes.